PATHOGENETIC RELATIONSHIP BETWEEN PERIODONTITIS, CHRONIC TONSILLITIS, AND SYSTEMIC DISEASES - Djuraeva Ferangiz Khakimovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: The interrelationship between periodontitis, chronic tonsillitis, and systemic diseases represents a complex pathogenic network involving microbial, immunological, and inflammatory mechanisms. Periodontitis and chronic tonsillitis are chronic infectious conditions characterized by persistent inflammation and bacterial colonization, which may act as reservoirs of pathogenic microorganisms and inflammatory mediators. These conditions can contribute to systemic dissemination of bacteria and toxins, influencing the progression of various somatic diseases such as cardiovascular disorders, diabetes mellitus, and autoimmune conditions. This article examines the shared etiological factors, immune responses, and molecular pathways underlying their connection, emphasizing the importance of integrated diagnosis and treatment strategies in modern clinical practice.